Peran Pemerintah Daerah Dalam Mengembangkan Potensi Pariwisata Kejuaraan Dunia F1 Powerboat (F1H20) Danau Toba Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat Kabupaten Toba Balige Sumatera Utara - Holmes Rajagukguk; Juandi Nababan; Bonari Tambunan; Musrafidin Simanullang; Lamma Sihotang (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Community welfare is a condition that shows the state of society's life which can be seen from the standards of that society. There are several sectors that can contribute income to improving community welfare. One of them is the Lake Toba F1H2O Tourism Sector which took place in Toba Balige district. The purpose of this research is to find out the role of the regional government in developing the tourism potential of Lake Toba carried out by the Toba Regency Tourism Office in improving community welfare through F1H2O which takes place in Toba Balige Regency, North Sumatra. The results of this research are expanding employment opportunities; Increased business opportunities; Increase income; The local culture is known by tourists. With the F1H2O event, the surrounding community is able to preserve and revive several traditional cultural patterns such as arts, handicrafts, dance, music and clothing typical of Toba district and increased tourist visits, infrastructure development: the F1 Powerboat world championship, the construction or improvement of infrastructure around the lake Toba, such as racing facilities, spectator stands, hotels, homestays, restaurants and transportation facilities. This development effort opens up new job opportunities for local communities and increases local income, economic diversification, increasing community income, promotion and introduction of local culture and also economic growth creates a positive circle for the welfare of society as a whole.